Exploitation of ZnO/Fe3O4 and TiO2/Fe3O4 nanocomposites on the degradation of organic compounds - Tan, Thian Khoon (2019)
Water is the main sources for all living beings. However, with the vast development and advancement of technology, water resources have been seriously contaminated by industries effluent, especially organic dyes. Various methods have been implemented to achieve certain level of acceptable cleanliness. Current most efficient and cost effective process is the photocatalytic process using highly photoreactive ZnO and TiO2 semiconductors. However, separation of the semiconductor powder arises at the end of the decomposition process. Therefore, there have been many researches trying to dope magnetic material into the semiconductor to make it easily separable and cost effective by just applying a magnetic field. However, most of the preparations require various recalcitrant and toxicant precursor chemicals as well as high sintering temperature. In light of these, this study has tried to use simple method of preparation and followed by a significantly moderate sintering temperature. The ZnO/Fe3O4 and TiO2/Fe3O4 nanocomposite materials have been successfully prepared by simple mechanical mixing and sintered at significantly moderate temperature of 300 and 350 oC, respectively. Besides, the prepared nanocomposite exhibit remarkable photocatalytic decomposition on few chosen dyes.